EAST ANTARTIC ICE STREAM TRIBUTARY UNDERLAIN BY MAJOR SEDIMENTARY BASIN - Bamber J.L.; Shepherd T.; Siegert M.J.; Ferraccioli F.; Vaughan D.G.; Joughin I.; Rippin D.M. (My University, 2006)
Marine and rift sediments exert a fundamental control on ice stream flow in the West Antarctic Ice Sheet, and hence on its mass balance and stability. In contrast, most ice streams in the much larger East Antarctic Ice Sheet are thought to be relatively stable features resting on till, perhaps underlain by crystalline rock. Any geological controls on East Antarctic Ice Sheet enhanced flow remain largely unknown. We present aerogeophysical evidence indicating that a region of enhanced ice flow in the interior of the East Antarctic Ice Sheet is underlain by subglacial sediments ~3 km thick and that these are influencing the flow regime of the overlying ice. We show that subglacial sediments are important in modulating ice dynamics, not just for the West Antarctic Ice Sheet, but also for its much larger neighbor, and suggest that the sedimentary basin identified here may contain information on the Neogene glacial history of this part of the East Antarctic Ice Sheet. © 2006 Geological Society of America.
Keywords: EAST ANTARCTICA; MAGNETICS; MARINE SEDIMENTS; SUBGLACIAL GEOLOGY; Neogene; Cenozoic::Neogene; Кайнозой::Неоген